Global Spread of Saemaul Undong for Rural Development in Developing Countries - 허장 (한국농촌경제연구원, 2016)
○ As growing attentions are paid to Korea’s Saemaul Undong, also known as the New Community Movement, around the world, an increasing number of non-Koreans take Saemaul Undong-related training programs, and relevant institutions have been organized in developing countries, with rural development policies designed by benchmarking Saemaul Undong. ○ In the UN General Assembly and the UN Sustainable Development Summit in 2015, the Saemaul Undong case of Korea was proposed as a new paradigm for international development cooperation, and accordingly, the Korean government released the Plan for Global Spread of Saemaul Undong on May 3rd, 2016. - The five key challenges include i) clarifying the concept of the Saemaul Undong ODA, ii) establishing strategies customized to each recipient country, iii) improving procedures and methods of projects, iv) improving the implementation system and efficiently allocating roles, and v) consolidating partnerships by expanding participation of stakeholders in the development process. ○ The Plan for Global Spread of Saemaul Undong has significance in that it presents the standards for Saemaul Undong ODA projects, which used to lack coherence in the past. Aside from the plans for the existing 24 key partner countries, the country-specific implementation strategies have been established with consideration for demands for development based on Saemaul Undong. In particular, the subcommittee has been organized under the International Development Cooperation Committee to take charge of systematic implementation, monitoring, evaluation and coordination of Saemaul Undong ODA projects. ○ The scale of Korea’s ODA projects has not reached the international standard level yet, but is rapidly growing. And as the number of ODA projects related to rural development has been on the rise, many relevant institutions, including the Korea International Cooperation Agency (KOICA), the Ministry of Agriculture, Food and Rural Affairs (MAFRA), the Rural Development Administration (RDA), and the provincial government of Gyeongsangbuk-do, have promoted Saemaul Undong-related or similar projects in the form of integrated rural development, development of customized agricultural technologies, and education and training programs for local residents. ○ The following points should be considered in applying the approaches of Saemaul Undong to the process of rural development in developing countries. - The concept, principles and detailed methodologies of Saemaul Undong should be abstractly outlined and defined as the Saemaul Rural Development Approach to be applied to a variety of today’s ODA projects. - ODA projects should serve not as another common type of aid project, but as the ones to actualize potential capacity of recipient countries, helping them autonomously develop subcategory projects based on the characteristics of and demands for development in target regions. - In order to employ the approaches of Saemaul Undong in ODA projects, the projects should be implemented by remaining consistent with international goals of development assistance such as SDGs and observing international regulations.